2003
DOI: 10.4049/jimmunol.170.11.5615
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Core and Nonstructural Protein 3 Proteins Induce Pro- and Anti-inflammatory Cytokines and Inhibit Dendritic Cell Differentiation

Abstract: Antiviral immunity requires recognition of viral pathogens and activation of cytotoxic and Th cells by innate immune cells. In this study, we demonstrate that hepatitis C virus (HCV) core and nonstructural protein 3 (NS3), but not envelope 2 proteins (E2), activate monocytes and myeloid dendritic cells (DCs) and partially reproduce abnormalities found in chronic HCV infection. HCV core or NS3 (not E2) triggered inflammatory cytokine mRNA and TNF-α production in monocytes. Degradation of I-κBα suggested involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
215
2
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(232 citation statements)
references
References 67 publications
10
215
2
5
Order By: Relevance
“…IL-10 is produced by many cell types including dendritic cells (28,29), macrophages, monocytes, NK (30,31) and NKT-cells (32) with pleiotropic effects. For example, IL-10 can downregulate antigen processing by transporter-associated with antigen processing, MHC expression and IL-12 production by antigen-presenting cells (APC) (9,10), resulting in impaired T-cell proliferation, effector function and memory (33).…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is produced by many cell types including dendritic cells (28,29), macrophages, monocytes, NK (30,31) and NKT-cells (32) with pleiotropic effects. For example, IL-10 can downregulate antigen processing by transporter-associated with antigen processing, MHC expression and IL-12 production by antigen-presenting cells (APC) (9,10), resulting in impaired T-cell proliferation, effector function and memory (33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TNF-␣ synthesis is up-regulated in patients with HCV chronic hepatitis. 43,44 As inflammatory cytokines including TNF-␣ have been suggested to trigger HHV-6 reactivation, 30 it is possible that HHV-6 replication might increase in HCV carriers. In addition, Rogers et al 7 demonstrated that patients infected with HHV-6 are more likely to have hepatocellular carcinoma as an underlying disease; however, they also found that the frequency of HHV-6 infection was not different between HBV and/or HCV carriers and noncarriers.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to an involvement of innate immune responses in HCV-infected patients, so far there is contrasting evidence of either normal or reduced numbers or function of circulating myeloid or plasmacytoid DC [29][30][31][32]. Additional suggestion of the involvement of innate immune mechanism(s) in the establishment of chronic HCV infection derive from the description of NK cell dysfunction (inhibition) following CD16-mediated triggering when CD81 molecules on NK cells are bound to HCV E2 protein [33].…”
Section: Introductionmentioning
confidence: 99%
“…During Mycobacterium tuberculosis infection in vitro, NK cells control pathogen replication in monocytes via natural cytotoxicity receptor (NCR) killing [21], and removal of NK cells from the peripheral blood of patients with latent tuberculosis significantly reduces mycobacterium-specific CD8 + CTL function [22]. Similarly, the dysfunction of NK cells observed during HIV-1 infection [23,24] has been recently associated with decreased expression of the major NCR (NKp30, NKp46 and NKp44), with a significant level of peripheral NK cell activation and inefficient lysis of HIVinfected CD4 + T cells [25][26][27][28].With respect to an involvement of innate immune responses in HCV-infected patients, so far there is contrasting evidence of either normal or reduced numbers or function of circulating myeloid or plasmacytoid DC [29][30][31][32]. Additional suggestion of the involvement of innate immune mechanism(s) in the establishment of chronic HCV infection derive from the description of NK cell dysfunction (inhibition) following CD16-mediated triggering when CD81 molecules on NK cells are bound to HCV E2 protein [33].…”
mentioning
confidence: 99%